Synthesis, characterization and biological activity studies of mononuclear Pd(II) complexes derived from unsymmetrical ylides - sepideh samiee; Maryam Kolahi; Leila Shirali; salman Kordi (شیمی کاربردی روز, 2020)
Transition metal phosphine complexes have attracted great attention in recent years due to their potential applications in organic synthesis, catalysis, design of new antitumor, antiviral and antibacterial drugs. The unsymmetrical ylides [Ph2P(CH2)nPPh2CHC(O)C6H4(m-NO2)](n = 1 (Y1) and 2 (Y2)) were synthesized in the reaction of BrCH2C(O)C6H4(m-NO2) ketone with 1,2-bis(diphenylphosphino)methane (dppm) and 1,1-bis(diphenylphosphino)ethane (dppe), respectively. These ligands were also reacted with [PdCl2(COD)] (COD = 1,5-cyclooctadiene) to give the palladacycle complexes [PdCl2(Ph2P(CH2)nPPh2CHC(O)C6H4(m-NO2))] (n = 1 (1) and 2 (2)). Characterization of obtained compounds was performed by elemental analysis and IR, 1H, 13C and 31P NMR spectroscopies. The results showed that the coordination of ylide to metal center occurred through the ylidic carbon atom and phosphine group (P,C-coordinated). Biological properties of these compounds were evaluated by MTT, TBA and antioxidant enzyme activity on colon cancer cells (Caco-2). The obtained results demonstrate thatthe studied compounds can be used as an antitumor agent. Evaluation of the survival and activity of antioxidant enzymes in cells expressing the anticancer activity of the studied compounds is due to activation of the antioxidant system in the cells treated with the studied compounds.